Gender Differences in Reading Comprehension Abilities Among Undergraduate Students in English Texts - Khadka, Bishnu Kumar; Awasthi, Jai Raj (English Language Teaching Perspectives, 2025)
This study assesses the reading comprehension ability (RCA) of undergraduate students at Mid-West University, Nepal, focusing on gender and academic program differences. Employing a quantitative research design, data were collected using a reading comprehension test based on English fiction and non-fiction texts adapted from CEFR test items, each accompanied by ten multiple-choice questions. The sample comprised 342 students (43.2% female and 56.8% male) from six graduate schools. Descriptive and inferential statistical analyses were conducted to evaluate RCA across gender and academic programs. Findings revealed that most male and female students achieved an upper basic (A2) or lower independent (B1) level of reading proficiency. Gender-specific comparisons showed no significant differences in mean RCA scores (t = -0.941, p > 0.05). Across academic programs, no statistically significant variances in RCA were observed between genders, as supported by program-specific t-tests. The study found no significant gender differences in reading comprehension abilities (RCA) among students, with both male and female students showing moderate to good understanding of English texts. Despite individual variations in performance, the findings indicated that gender did not significantly impact RCA, aligning with previous research suggesting minimal gender differences in language comprehension. Notably, variations in RCA within each gender were attributed to individual factors such as motivation, exposure to English, and learning strategies. This study highlights the need for inclusive and personalized approaches to improving RCA, emphasizing individual learning needs over gendered interventions.